Laboratory investigation on short design wave extreme responses for floating hinged-raft wave energy converters - Jin, S.; Brown, S. A.; Tosdevin, T.; Hann, M. R.; Greaves, D. M. (Frontiers in Energy Research, 2022)
In offshore renewable energy design procedures, accurate predictions of extreme responses are required in order to design for survivability whilst minimising associated costs. At present, the established method for predicting extreme responses is to conduct a large number of long-duration simulations, which is practical only in cases where the structural behaviour is captured by a computationally efficient linear approach. Many applications, however, will require a nonlinear approach, which significantly increases the computational cost, and hence the time required to analyse a problem. Should high-fidelity numerical approaches be the appropriate analysis tool, the long-duration simulations are likely to be impractical and in many cases infeasible. Laboratory testing can be utilised to address this to some extent, but this still time-consuming and expensive from a financial perspective. Consequently, there has been considerable interest in the use of short design waves as an alternative method for speeding up the design process. Currently, standards advise that short design waves can be utilised in the design of fixed offshore structures, but application to floating offshore structures needs verification before it becomes an established procedure. This study considers application of single and constrained short design waves to a floating hinged-raft wave energy converter using a 1:50 scale physical modelling approach, and compares with equivalent irregular sea states. The single wave approaches considered here are “NewWave” and the “Most Likely Extreme Response” wave, which are derived from the frequency content of the wave spectrum and response spectrum, respectively. The constrained approach considered in this study is the “Conditional Random Response Wave,” where the Most Likely Extreme Response wave is embedded within a random short irregular background. Results show that the single wave approaches under-estimate the extreme loading for the hinge-angle and mooring system compared with the irregular and constrained approaches. The discrepancy between single and constrained waves implies that memory effects are non-negligible, and hence it is critical that they are accounted for when utilising short design waves for floating applications.